Circuito RLC com resistência variável como uma equação de hermite - Silva, Davi Ferreira de Lima (Universidade Federal Rural do Semi-Árido, 2019)
Given the great importance of electrical circuits in everyday life, the wide field of applications of these, it is extremely important to study these. With the intention of predicting how the circuits behave in their components, it becomes essential to try to approach more and more the theory behind these to the real world. It is important to remember that most natural phenomena are shown from mathematical modeling, just like in electrical circuits. Where much of these phenomena can be expressed in the form of a differential equation. In order to develop an equation that demonstrates how the RLC circuit behaves in real situations, a variable resistance that varies linearly over time has been adopted for it, unlike most literature. To make possible the solution of the equation, the equation of the circuit was modeled until it is expressed by the Hermite equation. After such modeling, knowing the solution of the Hermite equation, we arrived at the solution of the RLC circuit with variable resistance.
Keywords: Circuito RLC; Resistência variável; Equações diferenciais; Equação de Hermite; RLC circuit; Differential equations; Hermite equation; Variable resistance; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA